De novo ATP1A2 variants in two Chinese children with alternating hemiplegia of childhood upgraded the gene-disease relationship and variant classification: a case report - Danping Huang; Min Liu; Hongying Wang; Bingbing Zhang; Dongjing Zhao; Weihao Ling; Manli Wang; Jun Feng; Yiping Shen; Xuqin Chen (BMC, 2021)
Abstract Background ATP1A2 gene mutation has been indicated to cause alternating hemiplegia of childhood (AHC); however, limited evidence supports this relationship so far. Case presentation We reported two Chinese patients with de novo ATP1A2 variants (c.970G>A and c.889G>A). Both patients presented with episodes of alternating hemiplegia, seizures and mild developmental delay. Brain magnetic resonance imaging revealed abnormal signals in both patients. Conclusions The new genetic evidence we reported here strengthened the gene-disease relationship, and the gene curation level between ATP1A2 and AHC became "Moderate" following the ClinGen Standard Operation Procedure. Consequently, the two variants can be reclassified as likely pathogenic.